N-doped porous activated carbon from rubber seed shells (Hevea brasiliensis) as high-energy supercapacitor material - Daulay, Siti Rahma; Farma, Rakhmawati; Awitdrus, Awitdrus (Universitas Riau, 2024)
Biomass is an environmentally safe and cost-effective source of activated carbon (AC) for supercapacitors (SC). In this study, AC was generated using precarbonisation and activation with KOH using rubber seed shell (RSS) as a precursor. The electrochemical performance was investigated by cyclic voltammetry and galvanostatic charge-discharge determination and the ACs were characterised using FTIR analysis technique. RSS materials were prepared by varying calcination temperatures of 700°C, 800°C, and 900°C without doping. RSS800 shows a maximum specific capacitance of 190 F/g and has an energy density of 26.2 Wh/kg and a power density of 695.4 kW/kg at 1 A/g. Furthermore, melamine was used as an external dopant source for the N-doping process. The doped AC sample (RSS800-90) had a specific capacitance of 288 F/g and has an energy density of 40.9 Wh/kg and a power density of 515.4 kW/kg at 1 A/g in H2SO4 electrolyte. N-doped with melamine as nitrogen source was successfully incorporated into AC to produce high-performance electrodes for SC.